DETERMINATION OF PREVALENCE AND ANTIBACTERIAL ACTIVITY OF ESBL (EXTENDED SPECTRUM BETA-LACTAMASES) PRODUCING KLEBSIELLA SPECIES ISOLATED FROM RAW MILK OF DOON VALLEY IN INDIA - S. CHAUHAN; U. FAROOQ; V. SINGH; AJAY KUMAR (International Journal of Pharma and Bio Sciences, 2013)
Milk is a key contributor to improving nutrition and food security. The virtues of milk as a food have long been recognized by human beings. Milk is however a good medium for bacterial growth and an efficient vehicle for bacterial infection when consumed without boiling or pasteurization. The aim of the present study was to evaluvate the presence of ESBL producing Klebsiella species present in raw milk of Doon valley in India. The study was carried out from July 2007 to July 2008. A total of 100 samples of raw milk were collected from Doon valley. These samples were cultured and the isolated organisms were identified by standard bacteriological methods. A total of 27 samples were found to be positive for Klebsiella species. Further ESBL phenotypic screening was performed. All 27 isolates found ESBL producing. Isolated Klebsiella spp showed 96.29% susceptibility to imipenem followed by ciprofloxacin (62.96%), piperacillin/tazobactam combination (51.85%) and ciftazidime (18.51%). This study reveals that Klebsiella isolated from raw milk in Doon valley produce ESBL in large proportion. The imipenem antibiotic which was found highly sensitive to ESBL producing klebsiella isolates might be a drug of choice.